Current issues of staff motivation by the example of a tourism industry enterprise - V. D. Fadeev (Путеводитель предпринимателя, 2024)
In the presented article, the author examines the issues of personnel motivation management. Currently, no one doubts that the most important resource of any company is its employees, in this regard, the relevance of the topic of the scientific article is due to the extremely important role of motivating the workforce needed by the enterprise, since the success of any organization in modern conditions depends on its ability to maximize the use of available resources. Every company that is serious about personnel management issues tries to develop its own motivation management system for its employees.